HABITAT PERINDUKAN Ae. albopictus DI PANTAI PENGHULU AGUNG DAN SEKIP, AMPENAN, NUSA TENGGARA BARAT - Pita, Baiq Nuraini Ayu; Tresnani, Galuh; Suryadi, Bambang Fajar; Zamroni, Yuliadi; Kusuma, AA Ngurah Nara (University of Mataram, 2024)
Ampenan is one of a coastal area with a dense population in Mataram City. There are lots of people activity in Penghulu Agung and Sekip beach since they are the recreational area in Ampenan District, and therefore diseases transmission through mosquito bites becomes easily. The research aims are to determine the abundance and habitat characteristics of Aedes albopictus as a vector of dengue fever in Penghulu Agung and Sekip beach. This esearch is a descripftive explorative research using random sampling and explorative methods. According to research results it can be conclude that the relative abundance value of Aedes albopictus from both location is 53.80% (high). The breeding habitat mostly in the form of bucket and boat with a dense of vegetation or canopi. environmental factors in the research location such as water temperature range between 29.8 - 30.5 Celcius, air temperatur between 25.5 - 29.9 Celcius, humidity between 52 - 76%, water acidity 6 - 8, salinity 0%, and light intensity 105 - 30,430 lux.